2021
DOI: 10.1542/peds.2021-050920
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment of Children With Disabilities

Abstract: Over the past decade, there have been widespread efforts to raise awareness about maltreatment of children. Pediatric providers have received education about factors that make a child more vulnerable to being abused and neglected. The purpose of this clinical report is to ensure that children with disabilities are recognized as a population at increased risk for maltreatment. This report updates the 2007 American Academy of Pediatrics clinical report "Maltreatment of Children With Disabilities." Since 2007, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 50 publications
2
23
0
2
Order By: Relevance
“…It was found that child welfare-involved youth with borderline-to-mild intellectual disabilities reported significantly greater dating violence victimisation and perpetration, compared to youth with average IQs ( 78 ). Children with disabilities are at greater risk of experiencing child maltreatment, with three times the higher prevalence of maltreatment than the typically developing population ( 95 ). When considering the whole child welfare system, ~50% of children investigated by CPS had a developmental disability(ies) ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that child welfare-involved youth with borderline-to-mild intellectual disabilities reported significantly greater dating violence victimisation and perpetration, compared to youth with average IQs ( 78 ). Children with disabilities are at greater risk of experiencing child maltreatment, with three times the higher prevalence of maltreatment than the typically developing population ( 95 ). When considering the whole child welfare system, ~50% of children investigated by CPS had a developmental disability(ies) ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children with disabilities are at greater risk of experiencing child maltreatment, with three times the higher prevalence of maltreatment than the typically developing population ( 95 ). When considering the whole child welfare system, ~50% of children investigated by CPS had a developmental disability(ies) ( 95 ). More concerning is the understanding that maltreatment rates are likely higher than reported, as those with disabilities may experience communication difficulties that hinder disclosure or self-report to caseworkers or practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Contributors to this increased risk include the added financial and emotional stress that caring for CYSHCN places on caregivers. 25 The Western Trauma Association and the Pediatric Trauma Society recognize the increased risk of abuse in CYSHCN and therefore list chronic medical conditions as a red flag when evaluating a child for abuse. 27 In older children, while abuse can still occur, bullying and crime victimization also likely play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Within the trauma system, CYSHCN are at greater relative risk of assault, and this finding holds across all age groups. Maltreatment of children with disabilities has been documented in the literature for CYSHCN generally, as well as for specific diagnoses such as autism spectrum disorder 24–26 . Contributors to this increased risk include the added financial and emotional stress that caring for CYSHCN places on caregivers 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation